2014
DOI: 10.1108/cdi-10-2013-0123
|View full text |Cite
|
Sign up to set email alerts
|

Role models: expatriate gender diversity pipeline or pipe-dream?

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…Affinity networks offer support and career advice and create connections within identity groups such as pregnant women (Dobbin et al, 2011). In addition, previous studies found that women are often not aware of the fact that they may function as role models for other women (Shortland, 2014). Both women themselves, as well as their organizations, may want to identify women who could act as role models and make them more visible and available to others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Affinity networks offer support and career advice and create connections within identity groups such as pregnant women (Dobbin et al, 2011). In addition, previous studies found that women are often not aware of the fact that they may function as role models for other women (Shortland, 2014). Both women themselves, as well as their organizations, may want to identify women who could act as role models and make them more visible and available to others.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of role models for career progression has been well established in the literature (Shortland, 2014). It is particularly the case for women that role models can help them to see how others have dealt with similar issues (Sealy and Singh, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, the extant literature has concentrated on a number of factors that potentially contribute and combine to reduce women's ability to work abroad. These include: gender bias in selection processes (Harris, 2002); perceived negative host country receptivity (Paik & Vance, 2002); lower access than their male corporate colleagues to support networks (Linehan, 2001), mentors (Linehan & Walsh, 1999) and role models (Shortland, 2014); dual careers, male career prioritisation and male family power (Dupuis, Haines & Saba, 2008;Harvey, 1998;van der Velde et al, 2005); difficulties faced by male 'trailing spouses' (Punnett, Crocker & Stevens, 1992); and children's education, health and welfare concerns (Dupuis et al, 2008). Very little, however, has been written specifically on the types of assignments offered by employers and the effects that these might have on women's willingness and ability to engage in different lengths and patterns of expatriation.…”
Section: Expatriate Gender Diversitymentioning
confidence: 99%
“…This research examines one specific aspect of human resource policy that relates to access to expatriate roles, namely the management of performance and development reviews, set within the context of the oil and gas industry. Although oil and gas employs high and increasing volumes of organisationally assigned expatriates compared with other industries (Air Inc., 2017), women comprise just 7-10 per cent of its upstream exploration and production expatriate population (Shortland, 2014a). The choice of this sector as a research case might appear to be an extreme, not widely applicable, example given its geographically isolated locations and the relative slowness with which women's share of expatriate roles has changed.…”
Section: Introductionmentioning
confidence: 99%